2004
DOI: 10.1046/j.1076-0512.2003.30055.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of Treatment of Resistant Port-Wine Stains With Variable-Pulse 595-nm Pulsed Dye and 532-nm Nd:YAG Lasers

Abstract: In individual patients, it may be effective to treat resistant PWS with the variable-pulse width 595-nm PDL and the 532-nm Nd:YAG laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…39 This is in good agreement with our prediction of H epi = 19.3 J/cm 2 in fair Caucasian skin (at t p = 1 ms). According to our simulation, the above radiant exposure value would cause problems in patients with moderately pigmented Asian skin (H epi = 9.9 J/cm 2 ), but these would probably have been categorized as phototype V and thus not enrolled in the study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…39 This is in good agreement with our prediction of H epi = 19.3 J/cm 2 in fair Caucasian skin (at t p = 1 ms). According to our simulation, the above radiant exposure value would cause problems in patients with moderately pigmented Asian skin (H epi = 9.9 J/cm 2 ), but these would probably have been categorized as phototype V and thus not enrolled in the study.…”
Section: Discussionsupporting
confidence: 81%
“…In another clinical study at 532 nm, 39 radiant exposure of 7 J/cm 2 (t p = 2 ms, d b = 3 mm) was applied with contact cooling of skin, with no adverse effects observed in the patients. Our simulation results indicate H epi = 14.2 J/cm 2 for fair Caucasian and 7.6 J/cm 2 for moderately pigmented Asian skin, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It does however have relatively high specificity for oxyhaemoglobin absorption. Previous studies using a KTP laser to treat CMs have similarly focused upon patients who have previously been treated with the PDL [7,8]. These have indicated a varying degree of response to treatment, with one study reporting a 14% response rate [7], whilst the other reported a 53% response rate [8].…”
Section: Response Of CM Colour To Test Patchesmentioning
confidence: 99%
“…However, complete CM clearance rates have remained around 15% despite the use of later generation PDL's with longer wavelengths and deeper penetration [1]. Therefore other laser and non-laser systems have been used in an attempt to improve CM clearance, including intense pulsed light (IPL) [2][3][4][5][6], the KTP laser [7,8], and the long-pulsed Nd:YAG laser [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical studies and experience using both approaches either alone or in combination have shown only little further therapeutic benefit. 22 Further treatment with PDL at lower subpurpuric fluences (6-7 mJ/cm 22 ) with no immediate or transiently appearing but rapidly fading purpura, usually combined with slightly longer pulse durations ranging from 3 to 6 milliseconds Using pulse stacking (2-3 consecutive pulses applied immediately after the preceding pulse to the same spot 23 ) may produce further lightening of PWS. The theory is that cumulative gentle heating may produce overall greater capillary heating and, hence, more efficient capillary wall damage than that achievable by a single high-energy short duration purpura-inducing pulse of laser light.…”
Section: Current Management Of Pdl-resistant Pwsmentioning
confidence: 99%